Climatology of Frequency, Life Period, Energy and Speed for Tropical Disturbances and Cyclones over the Bay of Bengal (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Tropical disturbances and cyclones are regularly formed at the Bay of Bengal basin. There are some common traits in them, albeit each one of them is unique. Discerning climatology for the basic features of any tropical cyclone is useful in numerous ways. This research has attempted to find a climatology for frequency, life period, energy, and speed for the tropical cyclones formed at the Bay of Bengal over a period of 31 years – from 1990 to 2020. The results elicit that there are marked changes in these aforementioned features. The total frequency, accumulated duration, and combined energy have escalated over the years. To be precise, these changes have taken effect more rigorously for the Post-monsoonal tropical cyclones. The overall translational speed has slightly diminished in recent years, except for the translational speed of cyclones formed during Pre-monsoon. These changes will have major ramifications on the lives and livelihoods of people, more so for those living in coastal areas. Hence, necessary actions are required to cut the probable losses and damages.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(1), 2021, P 23-31